Gastrointestinal Stromal Tumor in Sigmoid Colon at a Tertiary Care Hospital: A Case Report - Saha, Pankaj Kumar; Roy, Ratna; Saha, Haridas; Rahman, Md Mamunur; Haq, Mohammad Mahmudul; Bulbul, Surayea (Journal of Shaheed Suhrawardy Medical College, 2013)
Gastrointestinal stromal tumors (GISTs) are the mesenchymal tumors representing the most common mesenchymal neoplasm of gastrointestinal tract. However, GIST is recognized tumor entity and the literature on these stromal tumors has rapidly expanded. This present case report has been found in Dhaka at a tertiary care hospital in a male patient. The patient was operated at the local area before admitted at this hospital where he was misdiagnosed. In this hospital the diagnosis was confirmed by histopathologically. Surgical resection was performed laparoscopically by a skilled surgical team. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16224 J Shaheed Suhrawardy Med Coll, 2013;5(1):59-62